WHO JUDGES THE JUDGES? ADDRESSING INTEGRITY AND SECURITY GAPS IN THE SINDH JUDICIAL RECRUITMENT SYSTEM - Siddiqui, Hasan Rasheed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2019)
The transparency, fairness, and adequacy of the criteria used to select candidates for the position of Additional Sessions Judge (ASJ) in Sindh have long been a source of concern. Given the ASJ’s critical role in adjudicating both criminal and civil matters, the integrity of the selection process is fundamental to upholding judicial standards. However, the current testing mechanism has faced criticism for its limited ability to effectively distinguish between candidates and its emphasis on theoretical knowledge at the expense of practical legal competence. Additionally, concerns have been raised about the subjectivity and potential biases in the selection of interview panel members.This paper examines the existing framework governing the ASJ recruitment process in Sindh, identifying systemic challenges and proposing actionable reforms. Key issues explored include the lack of transparency in exam administration, inconsistent levels of difficulty across examination papers, and insufficient emphasis on evaluating practical legal skills, which are essential to the judicial function. The study advocates for the implementation of clear, objective evaluation criteria and standardized procedures for both the written examination and interview stages. These reforms aim to minimize discretion and reduce opportunities for bias, ensuring the selection of the most competent and deserving candidates. Ultimately, this paper recommends a comprehensive overhaul of the ASJ recruitment system in Sindh to reinforce judicial integrity, promote merit-based appointments, and uphold the foundational principles of justice.